E-procurement management for successful electronic government systems - Ordóñez de Pablos, Patricia 1975-; Cueva Lovelle, Juan Manuel 1958-; Labra Gayo, José Emilio; Tennyson, Robert D. (Information Science Reference, 2013)
"This book enhances the understanding and collaboration in e-government and the role of information technologies in supporting the development of improved services for citizens" - Provided by publisher
Includes bibliographical references
Keywords: Government purchasing; Internet in public administration; Aufsatzsammlung